Neurocognitive functioning and radiologic changes in primary CNS lymphoma patients: results from the HOVON 105/ALLG NHL 24 randomized controlled trial. Issue 8 (9th February 2021) - van der Meulen, Matthijs; Dirven, Linda; Habets, Esther J J; Bakunina, Katerina; Smits, Marion; Achterberg, Hakim C; Seute, Tatjana; Cull, Gavin; Schouten, Harry; Zijlstra, Josée M; Brandsma, Dieta; Enting, Roelien H; et al.
Abstract: Background: To analyze the effect of treatment on neurocognitive functioning and the association of neurocognition with radiological abnormalities in primary central nervous system lymphoma (PCNSL). Methods: One hundred and ninety-nine patients from a phase III trial (HOVON 105/ALLG NHL 24), randomized to standard chemotherapy with or without rituximab, followed in patients ≤60 years old by 30-Gy whole-brain radiotherapy (WBRT), were asked to participate in a neuropsychological evaluation before and during treatment, and up to 2 years posttreatment. Scores were transformed into a standardized z -score; clinically relevant changes were defined as a change in z -score of ≥1 SD. The effect of WBRT was analyzed in irradiated patients. All MRIs were centrally assessed for white matter abnormalities and cerebral atrophy, and their relation with neurocognitive scores over time in each domain was calculated. Results: 125/199 patients consented to neurocognitive evaluation. Statistically significant improvements in neurocognition were seen in all domains. A clinically relevant improvement was seen only in the motor speed domain, without differences between the arms. In the follow-up of irradiated patients ( n = 43), no change was observed in any domain score, compared to after WBRT. Small but significant inverse correlations were found between neurocognitive scores over time and changes in white matter abnormalities (regression coefficients: −0.048 to −0.347) and cerebral atrophy (−0.212 to −1.774). Conclusions: Addition of rituximab to standard treatment in PCNSL patients did not impact neurocognitive functioning up to 2 years posttreatment, nor did treatment with 30-Gy WBRT in patients ≤60 years old. Increased white matter abnormalities and brain atrophy showed weak associations with neurocognition.